Comparison Study of Solgel and Combustion Method for Synthesis Nano Spinel MgFe2O4 and its Influence on Electrochemical Activity. (2018) - Shetty, Krushitha; Nagaswarupa, H.P.; Rangappa, Dinesh; Anantharaju, K.S.; Surendra, B.S.; Kumar, Anil
Abstract: Spinel MgFe2 O4 nanoparticles (NPs) were prepared by solution combustion synthesis (SCS) and sol-gel methods. Solgel and SCS were followed by using Citric acid and ( oxalyl dihydrazide) ODH respectively. X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), were used to study the effect of synthesis methodology on the behavior of synthesized NPs. Differences in crystallinity, particle size and electrochemical activity of the ferrite NPs prepared by different methods were observed. XRD pattern of NPs obtained by both methods confirmed spinel phase structure of the prepared NPs with average size ranging from 13-22nm respectively. The flake like morphology was seen for all the prepared NPs. FTIR supports the absorption value of octahedral and tetrahedral sites. The MgFe2 O4 NPs prepared by sol-gel method revealed better electrochemical property with less charge transfer rate